A shared research agenda for landuse, landuse change, forestry and clean development mechanism: developed through an international workshop held 6-8 March, 2001, Bogor, Indonesia (Center for International Forestry Research, 2001)
About 20% of global greenhouse gas emissions are from landuse, landuse change and forestry (LULUCF) and mostly are from deforestation in the tropics. In March 2001 the Centre for International Forestry Research facilitated an international workshop to identify a global agenda of high priority research questions key to research areas related to the Clean Development Mechanism (CDM) and LULUCF. This document summarizes the workshop report that discussed the following issues: Capacity building and information sharing are critical for building support and political will for backing LULUCF projects; Scale was identified as a main issue in the current negotiation process; A global overview and evaluation of the potential for different CDM options is needed to provide insight into scale issues; The need to reduce costs was identified and set up as the main agenda for further research; Solving the problems of permanence is crucial if forestry projects are to be included in the protocol; Leakage is one of the main concerns raised by negotiators and other stakeholders opposed to the inclusion of LULUCF in the CDM; The production of forest carbon requires consistent, reliable and verifiable monitoring; A reliable, verifiable and cost-effective baseline is needed to calculate the additional certified emissions reduction (CER) accruing to CDM. A number of broader research topics were identified.